Food Safety Practice and Its Associated Factors among Meat Handlers in North Shewa Zone, Oromia, Ethiopia - Samuel Chane Teferi (International Journal of Food Science)
Background. Foodborne illness is one of the major public health problems globally. The majority of foodborne diseases arise from foods of animal origin. Hence, this study was proposed to evaluate meat handling practices and associated factors working in butcher shops in North Shewa Zone. Methods. Data were collected through face-to-face interviews using a pretested structured questionnaire. Data were entered into a computer and analyzed using SPSS version 26. Binary logistic regression was used to identify factors associated with meat handling practice. Result. The majority, 128 (57.1%), of meat handlers smoke in workplaces, and 20 (8.9%) of meat handlers handled money while processing meat. 180 (80.4%) of meat handlers process/handle meat when they had cuts, wounds, bruises, or injuries on their hands. 12.1% and 15.6% of meat handlers took food safety training and medical checkups, respectively. 51.3% of meat handlers had good meat handling practices. Knowledge (adjusted odds ratio [AOR] 2.99, 95% confidence interval [CI] 1.73-5.15), attitude (AOR=1.94, 95% CI: 1.12-3.37), experience (AOR=4.27, 95% CI: 2.34-9.85), medical checkup (AOR=3.87, 95% CI: 1.67-8.96), and educational status (AOR=5.50, 95% CI: 1.05-28.75) were significantly associated with meat handling practices. Conclusions. Food hygiene training before employment and awareness creation for meat handlers should be strengthened. Routine inspections by responsible authorities are also recommended. Future studies should focus on the enumeration of bacterial load from utensils and meat handlers.